Effect of hysterectomy on anorectal and urethrovesical physiology. Issue 2 (February 1992) - Prior, A; Stanley, K; Smith, A R; Read, N W
Abstract : To investigate whether vaginal or total abdominal hysterectomy is associated with changes in anorectal and urethrovesical physiology, 26 women were studied before operation and six weeks and six months afterwards. The results showed a postoperative increase in both rectal and vesical sensitivity (p less than 0.01). Similar results were observed irrespective of the type of hysterectomy. No significant changes in rectal or bladder compliance were noted, and anal pressure and urethral pressure and length were unchanged after surgery. Whole gut transit was not affected by hysterectomy. Urinary symptoms occurred de novo in 6/26 women and gastrointestinal symptoms in 2/26 women. These results show that significant changes in rectal and vesical sensitivity occur after hysterectomy for benign disease. These persist for at least six months postoperatively but are not always associated with development of urinary or gastrointestinal symptoms.